Odpowiedzi

2010-03-30T16:28:02+02:00
A)5/3=a/2
3a=5*2
3a= 10
a= 10/3

b)3/10 = x/4
10x = 3*4
10x= 12
x = 12/10
x = 6/5

c) 7/14 =m 21
14m = 7*21
14m = 147
m = 147/14

d)2/m = 3/7
3m = 14
m= 14/3

e) 3/x =7/x=5
7x = 3x+15
7x - 3x= 15
4x = 15
x = 15/4

f)m+4/2=m-3/5
2m-6=5m+20
2m-5m = 20+6
-3m=26
m = -26/3

g)a+3/5=7/5
5a+15=7*5
5a = 35 - 15
5a= 20
a = 4

h) x-2/3 =2x+7/5
6x+21=5x-10
x = -31

5/2m+5=2/4m-1
20m-5=4m+10
16m=15
m = 15/16
29 3 29
Najlepsza Odpowiedź!
2010-03-30T16:28:19+02:00
A)5/3=a/2 (stosujemy metodę na "krzyża")
3a= 5*2
3a=10/:3
a = 3⅓

b)3/10=x/4
10x=3*4
10x=12/:10
x = 1,2

c)7/14=m/21
14m=7*21
14m=147/:14
m=10,5

d)2/m=3/7
3m=2*7
3m=14/:3
m=4⅔

e)3/x=7/x+5
7x=3(x+5)
7x=3x+15
7x-3x=15
4x=15/:4
x=3,75

f)m+4/2=m-3/5
2(m-3)=5(m+4)
2m-6=5m+20
2m-5m=20+6
-3m=26/-3
m= -8⅔

g)a+3/5=7/5
5(a+3)=7*5
5a+15=35
5a=35-15
5a=20/:5
a=4

h)x-2/3=2x+7/5
5(x-2)=3(2x+7)
5x-10=6x+21
5x-6x=21+10
-1x=31/-1
x=-31

i)5/2m+5=2/4m-1
5(4m-1)=2(2m+5)
20m-5=4m+10
20m-4m=10+5
16m=15/:16
m=15/16
38 4 38